The Relationship Between Per Capita Income, Uninsured Rates, and Cardiovascular Mortality in Georgia Between 1994 - 2016 - Monique Bethel; Mark Thompson; Adam Berman (Georgia Southern University, 2019)
Background: The association between cardiovascular mortality, per capita income and uninsured rates in Georgia have not been well described. Methods: Cardiovascular mortality rates, per capita income and uninsured rates were obtained for the years 1994-2016, and their relationships were analyzed using univariate and multivariate statistical techniques. Results: In bivariate analysis, a strong inverse relationship between cardiovascular mortality and per capita income (r = -0.917, p < 0.0001) was detected, while bivariate analysis detected no relationship between cardiovascular mortality and uninsured rates. Both per capita income and uninsured rates were negative predictors of cardiovascular mortality in multivariate analysis. Conclusions: Per capita income increases in Georgia were strongly correlated with reductions in cardiovascular mortality. While there was not a linear correlation of healthcare coverage status and cardiovascular mortality, it demonstrated a protective effect in multivariate analysis. Keywords: Cardiovascular mortality, uninsured, per capita income